Taxing hard-to-tax markets - Arbex, Marcelo Aarestru (2014)
Tax enforcement costs constrain the government s ability to observe economic transactions, giving rise to hard-to-tax (HTT) markets. In these markets transactions are untaxed and consumers are better o¤ than in taxed markets. This paper studies a novel approach to combat evasion in HTT markets: consumer auditing, which rewards consumers for re- questing transaction receipts. We develop a Hotelling-type spatial model of sales taxation to analyze the welfare and distributional e¤ects of the implementation of this policy. We and that consumer auditing allows for a lower tax rate and greater provision of the public good in the economy. We show that this policy not only can enhance welfare, but also equalize utilities of consumers across markets